PURWARUPA SISTEM MONITORING KENDALI PAKAN IKAN BERBASIS WEB DAN RASPBERRY PI - Komarudin; Yuggo Afrianto; Prakosa, Bayu Adhi; Hendrawan, Ade Hendri (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2022)
The hobby is an activity that is usually done by humans, keeping fish in an aquarium, for example. However, busyness or activities that have become routine often become obstacles when distributing these hobbies. For example, when someone has to travel far but still has to maintain his hobby of keeping fish to condition his pets and provide appropriate feed. Therefore, this research makes a prototype tool that can make it easier for hobbyists by monitoring fish and feeding them directly. This study uses several stages of research, including the analysis stage, the design stage, the implementation stage, and the testing stage. The results of this study are monitoring of fish conditions can be seen directly via the web by streaming. The results of testing the control of fish feeding are where the feed reservoir volume is 100 grams optimally when adjusting the feed opening and closing using a servo motor setting shifted 10 degrees and open for 4 seconds to produce feed—weighing 4 grams that fell into the aquarium